Ratio between heat and mass transfer when concentrating the solution in a cooling tower - Tseitlin, Musii; Raiko, Valentina (Lviv Polytechnic National University, 2019)
The ratio between the intensity of the mass transfer in gas and the heat transfer in liquid during the evaporative solution concentration has been studied. It was determined that the share of liquid resistance in the total resistance to enthalpy transfer increases in the temperature range from 30 to 50°C by almost 2 times, and reaches 40 %. The technique has been developed for the separate determination of the mass transfer coefficients in gas and heat transfer in liquid.

Досліджено співвідношення між інтенсивністю масопереносу в газі та передачею тепла в рідині під час концентрації випарного розчину. Встановлено, що частка опору рідини в загальному опорі переносу ентальпії зростає в діапазоні температур від 30 до 50 ° С майже в 2 рази, досягає 40%. Розроблена методика для окремого визначення коефіцієнтів масопереносу в газі і теплопередачі в рідині.
Співвідношення між теплопередачею і масою при концентрації розчину в градирні
Keywords: concentrating solution; cooling tower; mass transfer; heat transfer; resistance to enthalpy transfer; step phase contact; fall-through trays